CALCULATION OF THE TEMPERATURE DEPENDENCE OF MAGNETORESISTANCE OSCILLATIONS IN NANOSTRUCTURED SEMICONDUCTORS (Web of Technology: Multidimensional Research Journal, 2026)
In this work, the temperature dependence of transverse electrical conductivity and magnetoresistance oscillations under the influence of a quantizing magnetic field in heterostructures based on In₀.₅₂Al₀.₄₈As/In₀.₅₃Ga₀.₄₇As/In₀.₅₂Al₀.₄₈As quantum wells is analyzed. At low temperatures (T = 4.2 K), sharp oscillations in magnetoresistance are observed due to the discrete structure of Landau levels. As the temperature increases, the oscillation amplitude decreases, and when approaching 40 K, quantum effects disappear due to thermal broadening. A decrease in the quantum well thickness leads to an increase in the oscillation amplitude.